Pathological and molecular analysis of Turkey coronavirus replication in captive wild Turkey embryos (broad-breasted bronze breeder) - Gomes, Deriane E. [UNESP]; Rosa, Ana C. G. [UNESP]; Nobrega, Daniela F. [UNESP]; Garcia, Andrea F. [UNESP]; Brandão, Paulo E.; Cardoso, Tereza C. [UNESP] (My University, 2011)
The degree of genetic and pathologic variation exhibited by a turkey Coronavirus (TCoV) strain was investigated after nine serial passages in 25-day-old turkey embryos obtained from wild broad-breasted bronze breeders. In spite of spleen, liver, kidneys, cloacal bursa and thymus have been collected and analysed, the main histopathological changes were only documented in the intestine sections. Microscopic lesions were characterized as mild enteritis, low degree of enterocyte vacuolization and detachment of the intestinal villous after five consecutive passages and were considered absent in the last passages. Genealogic analysis based on S1 and S2 DNA sequences suggested that Brazilian isolate might be considered as originated from TCoV strains circulating in the United States, as 100% identity with TCoV-Gl strain. Although S1 S2 sequences from each passage revealed no significant point mutations, and no correlation could be speculate between S2 nucleotide changes and pathologic features in infected embryos. This is the first demonstration of wild turkey embryos as a model for TCoV isolation and propagation.
Keywords: Pathology; Spike gene; Turkey coronavirus; Wild turkey species